Dr. James Kinyangi discusses a new agriculture program - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Dr. James Kinyangi,Regional Program Leader CCAFS (Climate Change, Agriculture and Food Security) - East Africa discusses a about new agriculture program Video by Meerim Shakirova, social media reporter